Antithrombotic drugs in secondary stroke prevention among a community dwelling older population. Issue 8 (21st July 2003) - Landi, F; Cesari, M; Onder, G; Zamboni, V; Lattanzio, F; Russo, A; Barillaro, C; Bernabei, R
Abstract : Background: Patients who suffer a cerebrovascular event are at high risk of a recurrence. Secondary prevention is crucial in reducing the burden of cerebrovascular disease. Objective: To estimate the percentage of stroke survivors receiving antiplatelet or anticoagulant drugs and to identify factors associated with such treatment. Design: Cross sectional retrospective cohort study. Methods: Data were analysed from a large collaborative observational study, the Italian "silver network" home care project, which collected data (from 1997 to 2001) on patients admitted to home care programmes (n = 5372). Twenty two home health agencies participated in evaluating the implementation of the minimum dataset for home care (MDS-HC) instrument. For the present study, 648 individuals with a diagnosis of stroke were selected and the initial MDS-HC assessment reported. Results: 70% of stroke survivors did not receive any antiplatelet or anticoagulant drugs (95% confidence interval (CI), 66.5 to 73.5). Among all age categories, aspirin and ticlopidine were the two most commonly prescribed drugs. Living alone (odds ratio (OR), 0.49 (95% CI, 0.24 to 0.89)), dependency in activities of daily living (0.66 (0.40 to 0.99)), cognitive impairment (0.58 (0.38 to 0.86)), and low educational level (0.58 (0.34 to 0.98)) were associated with a reduced likelihood of receiving secondary stroke prevention treatment. Cardiac arrhythmias, coronary artery disease, heart failure, and peripheral vascular disease were associated with the use of antiplatelet or anticoagulant treatment. Conclusions: Negative attitudes among physicians with respect to secondary stroke prevention are prevalent and reinforce the need for increased awareness of existing data on the risks and benefits for elderly individuals. Social problems and functional impairment may be issues concerning physicians when deciding whether or not the risks of treatment exceed the benefit.